Abundance of Common Terns at Punta Rasa, Argentina: a major wintering area - Sapoznikow, Alexandra (2002)
The Common Tern (Sterna hirundo) breeds in North America and migrates to South America at the end of the northern summer. At Punta Rasa (Buenos Aires Province, Argentina) this species is present from November to April. Between December 1995 and March 1996, the peak numbers of 20,000 individuals were recorded in March. These numbers place Punta Rasa as one of the most important wintering sites in South America. The daily pattern of abundance was similar throughout the austral summer with a peak at dusk. Although tidal height did not alter this pattern, it determined the availability of roost sites, constraining the spatial distribution of terns.